Pop culture and entertainment in the twenty-first century - Gagne, Tammy (Defining events of the twenty-first century., 2020)
Explores different people, events, and artistic works that have helped to shape the culture of the United States in the twenty-first century. Includes fact boxes, source notes, and websites for future study.